Behind the scenes of the Old Testament : cultural, social, and historical contexts (Baker Academic, a division of Baker Publishing Group, 2018)
"This authoritative volume brings together a team of world-class scholars to cover the full range of Old Testament backgrounds studies in a concise, up-to-date, and comprehensive manner. With expertise in various subdisciplines of Old Testament backgrounds, the authors illuminate the cultural, social, and historical contexts of the world behind the Old Testament. They introduce readers to a wide range of background materials, covering history, geography, archaeology, and ancient Near Eastern textual and iconographic studies. Meant to be used alongside traditional literature-based canonical surveys, this one-stop introduction to Old Testament backgrounds fills a gap in typical introduction to the Bible courses. It contains over 100 illustrations, including photographs, line drawings, maps, charts, and tables, which will facilitate its use in the classroom."